Understanding the Place of Islamic Arbitration within the Nigerian Law - Kudirat Magaji W. Owolabi (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: For many years, Nigerian Muslims had long desired a wider use of Shari’ah outside its traditional usage in worship and family relations. This agitation has led to a rise in the use of Shari’ah in commercial transactions and banking and financial products lately. As the use of Shari’ah in this realm of commercial relationships increases, conflict is inevitable and this requires appropriate dispute resolution mechanisms to settle it. Not only that, Muslims in Nigerian wish to observe and be governed by Shari'ah in all aspects of their lives including their commercial dealings, they also desire a resolution of their disputes in accordance with their faiths and beliefs. Thus, the contemporary laws in Nigeria need to be merged with Islamic law principles in order to meet the demands of its citizens.Purpose/Objective Study: This paper aimed to examine the legal status of Islamic arbitration and its awards within the Nigerian legal framework particularly in area of commercial disputes.Design/Methodology/Approach: This paper employed doctrinal methodology of legal research. It therefore adopts descriptive and analytical methods. It involves primary sourcing materials from Quran, Sunnah, Acts and Cases. Secondary sources include journal articles, textbooks, official documents online and internet materials.Findings: This paper revealed that the notion of a tahkim (arbitration) subsists and recognise in the Shari’ah law and in Nigerian legal system. However, provisions of Arbitration and Conciliation Act (ACA) 1988 do not consider the idiosyncrasies of Islamic injunctions, despite growing investors’ interests in Islamic commercial transactions. ACA do not provide a Shari'ah compliant arbitration alternative for both Muslim and non-Muslim parties who are willing to arbitrate under the Islamic law. It is consequently suggested that peculiar nature of the Islamic arbitration and awards should be considered in the ACA and the relevant Sections should be amended accordingly.Paper Type: Research Article